ANALYTIC INVESTIGATION OF THE IMPRINTS OF CHARGE ON REISSNER NORDSTROM BLACK HOLE PHOTON RING - mugambi, james (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
Exquisite precision has been demonstrated in testing General Relativity (GR) in weak-field regimes; however, substantial absence of precise tests persists in strong-field regimes. Black holes serve as laboratories to scrutinize GR in strong-gravity regimes. Observations from a variety of cosmological probes consistently point to the existence of dark energy which is responsible for the universe's accelerating expansion. The cosmological constant provides an elegant explanation for this observed acceleration. Furthermore, it is possible to assume that black holes have charge making it vital to investigate how this affects their observational properties. The Reissner–Nordström black holes solution is the black hole metric that incorporates both charge and the cosmological constant. This research is dedicated to probing the nature of strong gravity for black holes in Reissner–Nordström spcaetime through the photon ring and other observables. The foundational part of our study begins with an exploration of the fundamental concept of photon orbits, serving as the basis for constructing the photon ring. Precise computations of time delays, Lyapunov exponents, and changes in azimuthal angle parameters will follow, providing insight into how they shape the structure of the photon ring.